El conocimiento de la educadora infantil: una aproximación a su construcción (Papeles, 2012)
This article is a contribution to reflection on how institutionalized practices in early childhood education have shaped the understanding of Child Educator (ChE) and how it should move to new constructions and understandings. This text show us some investigative movements interested in understanding the thought and action of the teacher, also develops historical questions of the evolution of the concept of childhood from different schools of thought and ideas. On the other hand, it highlights the origin of the ChE profession as one of the aspects that has hindered the creation of knowledge, and makes the difference of the elements that serve as a point of analysis to define the object of study of ChE. Through knowledge epistemological exploration of ChE makes a short work of a particular knowledge and another differentiable knowledge of other field teachers. Finally, using the idea of forming devices, the idea of knowledge desirable is developed to produce knowledge of the ChE and which relate to the principles of child education.
Keywords: Epistemology; Knowledge; Children’s Educator; Training; Practice; Teacher Knowledge; Reflection; Hyphens and routines